Gas exchange measurements and an indirect estimate of primary production in a holm-oak ecosystem - Manes, F; Vitale, M; Feoli, E; Scimone, M; Canfora, E (FRESENIUS ENVIRONMENTAL BULLETIN, 1998)
An original and simple primary production model is presented. Annual trends of the daily average values of net photosynthesis and leaf transpiration for helm oak are showed. Moreover, primary production data were obtained. To validate the model, an evaluation between estimated results and field measurements was performed, obtaining a strong correspondence.
Citation
Keywords: holm-oak; photosynthesis; plant simulation model; primary production; Transpiration